CORPORATE DEADLOCK AND PROTECTION MECHANISMS: THE ROLE OF CORPORATE AGREEMENTS (International Conference on Modern Science and Scientific Studies, 2025)
This research examines the significance and function of corporate agreements in protecting against deadlock situations from both theoretical and practical perspectives. The study comprehensively explores the legal nature of corporate agreements, international legislative experiences, and the current state of affairs in Uzbekistan. The paper analyzes the definition of corporate deadlock, its underlying causes, and the adverse effects on company operations. Through examining the preventive, regulatory, and protective functions of corporate agreements, the research investigates effective protection mechanisms against deadlock situations. Specifically, it explores opportunities for preventing disputes through pre-establishing rights and obligations among shareholders, creating action algorithms for conflict situations, and regulating voting procedures. The analysis of corporate agreement institutions in Uzbek legislation reveals deficiencies such as insufficient specialized regulatory frameworks and unclear practical implementation mechanisms. Based on research findings, practical recommendations have been developed for improving national legislation by incorporating international best practices.